What place for pastoral activities in the economic transformation of Vicdessos (Ariège Pyrenees)? - Pierre Dérioz; Maud Loireau; Philippe Bachimon; Églantine Cancel; David Clément (Revue de Géographie Alpine)
Once a major part of life in the mountain landscapes of Vicdessos (Ariège, southwestern France), pastoral activities were marginalized when industries brought full employment to the area. The “Pechiney era” (1906-2003) was characterized by the return of fallow lands and forests on the slopes and on some valley floors. Now that this small territory is engaged in a voluntary conversion oriented towards outdoor recreational activities (Montcalm nature-sports centre), the twenty or so livestock farms still in operation seem to be the best guarantors of the landscape resource on which tourist attraction depends (village surroundings, high mountain pastures). The creation of Pastoral Land Associations around some villages reflects the awareness of this issue by elected officials, and has led to permissions for the expansion of some farms and the creation of new ones. Even though the amount of livestock is sometimes insufficient to prevent the return of brush and trees to pastures and even though the farms, some of them in economically precarious states, do not visibly take part in the new tourism system, these livestock farmers are gaining recognition for their role as landscape managers. In addition, the increased direct sales of their products and the events they organize to enlighten people of their activities (fairs, transhumance celebrations) highlight their role – material as well as symbolic – in the territory’s development. However, the issue of modalities of access to grazing lands remains crucial for this pastoral renewal, which will, in any case, have to depend on innovations (diversification of livestock, short food-supply chains, agrotourism), especially when many older livestock farmers will soon retire.